Néron models in log mixed Hodge theory by weak fans - Kato, Kazuya; Nakayama, Chikara; Usui, Sampei (Proceedings of the Japan Academy. Series A. Mathematical sciences, 2010)
We construct Néron models of intermediate Jacobians in degenerations over higher dimensional bases by means of log geometry.